2009
DOI: 10.1136/gut.2009.183095
|View full text |Cite
|
Sign up to set email alerts
|

Trough serum infliximab: a predictive factor of clinical outcome for infliximab treatment in acute ulcerative colitis

Abstract: For patients with ulcerative colitis treated with infliximab, a detectable trough serum infliximab predicts clinical remission, endoscopic improvement and a lower risk for colectomy. An undetectable trough serum infliximab, irrespective of antibody status, is associated with less favourable outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
393
8
12

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 489 publications
(442 citation statements)
references
References 26 publications
29
393
8
12
Order By: Relevance
“…8 Observational studies have demonstrated a relationship between IFX and ADA drug concentrations, the presence of anti-drug antibodies and clinical outcome. [9][10][11][12] In the case of loss of response with low drug titres without antibodies, increasing the dose or shortening of the dosing interval is effective. 13 Whereas in cases of low drug titres due to anti-drug antibody formation, a switch to another anti-TNF is the preferable strategy.…”
Section: Introductionmentioning
confidence: 99%
“…8 Observational studies have demonstrated a relationship between IFX and ADA drug concentrations, the presence of anti-drug antibodies and clinical outcome. [9][10][11][12] In the case of loss of response with low drug titres without antibodies, increasing the dose or shortening of the dosing interval is effective. 13 Whereas in cases of low drug titres due to anti-drug antibody formation, a switch to another anti-TNF is the preferable strategy.…”
Section: Introductionmentioning
confidence: 99%
“…An initial trial in Belgium highlighted that patients with infl iximab concentrations >12 μ g/ml had a longer duration of response than those with lower drug levels ( 72 ). Several further studies also demonstrated that patients who have detectable trough infl iximab levels are likely to remain in remission compared with those with undetectable trough infl iximab levels ( 58,73,74 ). Similar studies have demonstrated the predictive value of adalimumab drug levels ( 75 ).…”
Section: Anti-tnf and Anti-integrin Therapymentioning
confidence: 66%
“…Multiple studies have confi rmed a correlation between clinical response and trough serum levels of anti-TNF medications [13][14][15][16][17]. Moreover, such correlation was recently established not only for clinical response but for endoscopic outcomes (mucosal healing) and decline of infl ammation markers [18][19][20][21].…”
Section: Risk Factors For Secondary Lormentioning
confidence: 97%
“…ATI interfere with the biologic activity by inhibiting the binding of the TNF-α inhibitors to both serum and membrane-bound [28,29]. Formation of ATIs has been demonstrated to be correlated with decreased levels of anti-TNFs and diminished clinical response, although not all studies support that [13][14][15][16]30]. Th is discrepancy may result from several factors, such as diff erent sensitivity of the employed assays (see below), non-neutralizing antibodies, non-anti-TNF-driven disease and alternative methods of elimination of anti-TNFs [1].…”
Section: Antibodiesmentioning
confidence: 99%